PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KOPERASI MEKKAR DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Erni Widajanti, Kristiana Asih Indrayanti, Alwi Suddin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study to determine the significance of the effect ofcommunication, working environment, motivation on employee performance and analyzethe influence of communication and work environment on employee performance andmotivation as a moderating variable. The data used qualitative and quantitative datasources using primary and secondary data. The population is all employees of theCooperative Mekkar PDAM Surakarta many as 48 people. Techniques of data collectionusing questionnaires, sampling technique used total sampling to all employees of theCooperative Mekkar PDAM Surakarta. Data were analyzed using classical assumptiontest, multiple linear regression analysis, t-test, F, R2 test, and test the absolute value ofthe difference. Based on the research results obtained communication and motivation tohave a significant effect on employee performance, but the work environment does notsignificantly influence employee performance and motivation does not moderate theinfluence of communication and work environment on employee performance.Keywords: communication, work environment, motivation, employee performance.